2y-9=13

Simple and best practice solution for 2y-9=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y-9=13 equation:


Simplifying
2y + -9 = 13

Reorder the terms:
-9 + 2y = 13

Solving
-9 + 2y = 13

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 2y = 13 + 9

Combine like terms: -9 + 9 = 0
0 + 2y = 13 + 9
2y = 13 + 9

Combine like terms: 13 + 9 = 22
2y = 22

Divide each side by '2'.
y = 11

Simplifying
y = 11

See similar equations:

| x-361-195+1236-22=599 | | 3x+5=x-5 | | 5v^2+21v-20= | | -72=-5(n+6)-7 | | x-152+419=794 | | 20v^3+105v^2-100v= | | 6x=8+7x | | 20=4(x+7) | | 4y+8=16 | | 3x-2x+8-10=7 | | 10+x=28 | | -4x-4+x-2y+7x= | | 2=3(x+7)+2 | | 4-(7n-5)+18n=5(5n+1) | | 25=-3k+5(k+7) | | 2x+3=19+5x | | x^2-0.3=-0.06x | | 9(2a-3)-5(3a-2)=-a+9(a-8) | | 5d-17-3d+18=15d+17-11d | | -8-4(2q-3)=-16 | | 7=-5(5+7n)-3 | | 7n-1=3k-5 | | -8(1+8a)=-8 | | 4x^2+18x+20=0 | | -(-7+1)=-(-3-8q) | | 8*(2x+1)-(11-2)*x=6 | | x-7y=-14 | | 0=14t^2+16t+1798 | | 6[x-2(2x+3)+1]+3(5+6x)+x=0 | | 1.76=a-2.84 | | x+x-2+x+1=62 | | 8x^2-4x-60=0 |

Equations solver categories